An introduction to the basic elements of the caste system of India - Goghari, Vina M.; Kusi, Mavis (Frontiers in Psychology, 2023)
Oppression, systemic bias, and racism have unfortunately long been part of the human experience. This paper is a review of basic elements of the Indian caste system, understanding its impact on the daily lives of different caste members, the role of colonialism in perpetuating the caste system, the Indian reservation system for mitigating disadvantages created by the caste system, and how categorization and labels can affect individual identity. This paper then discusses the global relevance of the caste system and its impact on mental health and psychological functioning. In India, the caste system is a comprehensive, systematized, and institutionalized form of oppression of members of the lower castes, particularly the Dalits. Formalized during the British colonial period, the caste system brings together two related Indian concepts of varna and jāti to create four social orders and multiple subunits. Sitting outside the traditional four orders are the Dalits, who experience social, economic, and religious discrimination due to an inherited status related to traditionally polluting occupations. Since the caste system extends beyond India to other South Asian countries, as well as to communities around the world that are home to the Indian diaspora, the inequities created by the caste system are a global issue. India’s affirmative action system provides important insights to policy makers, as well as researchers in the social sciences for how to counteract the effects of systematized oppression. Collectively, this can aid in a better understanding of the effects of discrimination and oppression on identity, self-esteem, and mental health, and how we can develop more targeted policies and procedures in our own local contexts.